Effect of grafting method on the physical property and antioxidant potential of chitosan film functionalized with gallic acid. (April 2019) - Zhang, Xin; Liu, Jun; Qian, Chunlu; Kan, Juan; Jin, Changhai
Abstract: Chitosan (CS) was functionalized with gallic acid (GA) by three different grafting methods including free radical initiation, carbodiimide coupling and tyrosinase catalysis. The obtained GA grafted CSs (GA-g-CSs) were further characterized and developed into films by casting. For the first time, effect of grafting method on the physical property and antioxidant potential of GA-g-CS films was investigated. Different grafting methods resulted in varied grafting ratios (41.80–125.88 mg/g). Three GA-g-CSs presented different ultraviolet (UV) and infrared spectra, indicating GA was conjugated with CS by different linkage patterns. CS and three GA-g-CS films had similar thicknesses and elongation at break. Among different films, GA-g-CS film obtained through carbodiimide coupling method showed the highest water vapor barrier property, tensile strength, thermal stability and 2, 2-diphenyl-1-picrylhydrazyl radical scavenging ability; whereas GA-g-CS film prepared by tyrosinase catalysis exhibited the darkest color and the highest UV light barrier property and opacity. Besides, three GA-g-CS films presented rougher surfaces and cross-sections than CS film. Our results suggested the physical property and antioxidant potential of GA-g-CS films were significantly affected by the grafting method and grafting ratio. Graphical abstract: Highlights: Chitosan was functionalized with gallic acid through three different grafting methods. Three synthesized gallic acid grafted chitosans (GA-g-CSs) had different structures. Grafting method and grafting ratio were factors affecting GA-g-CS films' property. GA-g-CS film prepared by carbodiimide coupling possessed the best performance.